Pengembangan Media Pembelajaran Monopoli untuk Materi Vektor - Sarah Aulia Oktaviani; Monika Clara Noviati; Setyani Intan Novitasari; Dhela Anindi Ramadhanti; Leonard Leonard (Journal of Instructional Development Research, 2020)
The purpose of this study is to develop media education based on monopoly games as a viable medium to help mathematics learning in high school. The research method used is ADDIE (Analyze, Design, Development, Implementation, and Evaluation). The results showed that this media education can increase student interest in learning and assist teachers in providing cognitive value and activeness. So, it can be concluded that the media education of mathematical monopoly for vector material is feasible to use.